TRADISI BARONGSAI DALAM MASYARAKAT TIONGHOA KEC.BANGKO KOTA BAGANSIAPIAPI - Rio Antoni; Hesti Asriwandari (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
This research is based on the shift of lion dance tradition in bagansiapi-api city. Problem formulation in this research are: (1)